Treatment of medulloblastoma using an oncolytic measles virus encoding the thyroidal sodium iodide symporter shows enhanced efficacy with radioiodine - Hutzen, Brian (BioMed Central, 2012)
BACKGROUND: Medulloblastoma is the most common malignant brain tumor of childhood. Although the clinical outcome for medulloblastoma patients has improved significantly, children afflicted with the disease frequently suffer from debilitating side effects related to the aggressive nature of currently available therapy. Alternative means for treating medulloblastoma are desperately needed. We have previously shown that oncolytic measles virus (MV) can selectively target and destroy medulloblastoma tumor cells in localized and disseminated models of the disease. MV-NIS, an oncolytic measles virus that encodes the human thyroidal sodium iodide symporter (NIS), has the potential to deliver targeted radiotherapy to the tumor site and promote a localized bystander effect above and beyond that achieved by MV alone. METHODS: We evaluated the efficacy of MV-NIS against medulloblastoma cells in vitro and examined their ability to incorporate radioiodine at various timepoints, finding peak uptake at 48 hours post infection. The effects of MV-NIS were also evaluated in mouse xenograft models of localized and disseminated medulloblastoma. Athymic nude mice were injected with D283med-Luc medulloblastoma cells in the caudate putamen (localized disease) or right lateral ventricle (disseminated disease) and subsequently treated with MV-NIS. Subsets of these mice were given a dose of (131)I at 24, 48 or 72 hours later. RESULTS: MV-NIS treatment, both by itself and in combination with (131)I, elicited tumor stabilization and regression in the treated mice and significantly extended their survival times. Mice given (131)I were found to concentrate radioiodine at the site of their tumor implantations. In addition, mice with localized tumors that were given (131)I either 24 or 48 hours after MV-NIS treatment exhibited a significant survival advantage over mice given MV-NIS alone. CONCLUSIONS: These data suggest MV-NIS plus radioiodine may be a potentially useful therapy for the treatment of medulloblastoma.